The acute effects from the use of weighted implements on skill enhancement in sport: a systematic review - Jermyn, S.; O'Neill, C.; Coughlan, E. K. (The Journal of Strength and Conditioning Research, 2021)
Weighted implements are used before competitive performance with the aim of enhancing motor skill execution on return to the standard implement. The purpose of this review was to analyze the existing literature pertaining to the acute effects of weighted implements on respective sporting performance. Following a systematic screening process, 25 studies were identified. This review highlighted the effects of (a) weighted balls and bats on throwing and batting performance and (b) indoor weight throw implements on indoor weight throw performance. Studies reported conflicting effects on immediate performance post-warm-up with the respective implements. Notably, although overweighted bats and overweight attachments are a prominent preparatory tool in baseball, this review found consistent and repeated evidence of degraded batting performance in striking-based studies. Decreased bat velocity, altered swing patterns, subjective-objective mismatches of bat speed and weight, temporal accuracy errors, and inadequate recalibration to the standard bat were identified as acute effects. This review identified an obvious dearth of research into the acute effects of weighted implements on motor skills in other sports with equally complex perceptual motor patterns, such as football (soccer), golf, rugby, basketball, and American football. Future weighted implement research should investigate the acute effects of respective implements on motor skill performance in other sports, such as those aforementioned, with the purpose of exploring relevant implications for preparatory strategies and immediate performance on return to the standard implement.